Outcomes following Microvascular Mandibular Reconstruction in Pediatric Patients and Young Adults - Shannon M. Malloy, BS; Wouter J. Dronkers, BSc; Joseph M. Firriolo, MD; Laura C. Nuzzi, BA; Maarten J. Koudstaal, MD, DMD, PhD; Bonnie L. Padwa, DMD, MD; Amir H. Taghinia, MD, MPH, MBA; Brian I. Labow, MD, FACS, FAAP (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. The etiology and treatment of complex mandibular defects in children differ markedly from those of adults, although treatment with free bone flaps is historical in both groups. While adult outcomes and complication rates are well known, few pediatric data exist, especially for patients with congenital deficiencies. This study reports early and late outcomes from a cohort of young, primarily syndromic patients undergoing microvascular mandibular reconstruction. Methods:. This is a retrospective case series of patients who underwent microvascular mandibular reconstruction between 1995 and 2016. Results:. Thirteen patients received a total of 13 fibula transfers and 1 medial femoral condyle transfer. Most patients carried a congenital diagnosis (77%), and the average age during surgery was 11.7 ± 5.7 years. The median (interquartile range) [IQR] length of follow-up was 6.3 (5.7) years. There was a 100% flap survival rate, although 86% of all patients experienced at least one complication. Half of all procedures resulted in an early complication. Nine patients (69%) developed late complications, of which temporal mandibular joint ankylosis was the most common (n = 5; 38%). Conclusions:. This study is one of few detailing outcomes following mandibular reconstruction by free flap transfer in pediatric patients. These patients were primarily syndromic with appreciable complication rates higher than in other adult and pediatric studies. Some complications are manageable or self-resolving, but others lead to functional problems that may require late operative interventions to correct. Microsurgical treatment should be reserved for children with large, complex mandibular defects when other options are unavailable or have been exhausted.